Body Dysmorphic Disorder : An Unusual Presentation of Schizophrenia - Patel, Amul (Medknow Publications, 2004)
Although body dysmorphic disorder is a psychiatric disorder in its own right, rarely it can be a variant of a variety of psychiatric syndromes like schizophrenia, mood disorders, OCD etc. Following is an unusual case report of a female patient who presented with body dysmorphic disorder later diagnosed as having schizophrenia.